Digital mapping of erosion degree of soils using the factor - property and factor - process - property models (the south of the Central Russian upland) - M. A. Smirnova; A. P. Zhidkin; N. I. Lozbenev; E. A. Zazdravnykh; D. N. Kozlov (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
Soil degradation resulting from water erosion poses a serious threat to food and environmental security, therefore the research of soil erosion features and soil erosion mapping do not lose their relevance. The paper presents the results of large-scale digital mapping of the erosion degree of the arable soils in the Prokhorovsky district of the Belgorod region (85 thousand hectares), based on two approaches: (1) linking the factors of erosion-accumulative processes and the erosion degree of soil directly (factor -property model), and (2) due to imitation erosion model WaTEM/SEDEM (factor - process - property model). The inclusion of the process component into the digital soil mapping algorithm allows taking into account not only the spatial but also the temporal soil erosion features. It was revealed that the agricultural development of the Prokhorovsky district was primarily carried out on lands that are weakly prone to erosion, with the rate of erosion almost two times lower than on younger arable lands. As a result, the soil erosion maps, based on the factor - process - property model, with and without taking into account the duration of agricultural use, largely correspond to each other. Dominant soil categories (the map pixel corresponds to one soil taxa - noneroded and slightly eroded, medium, highly eroded), mapping by factor -property and factor - process - property models, have a high degree of correspondence to each other (prediction identity for 90% of pixels), while the soil combinations (the map pixel has information on the proportion of soils with different erosion degrees of soil) more significant (identity for less than 60% of pixels). The areas of zonal, erosion-zonal, and weakly eroded soil combinations differ 1.5-2 times, in the direction of a greater degree of soil erosion on the factor - process - property map.